Oketani Massage on the Continuity of Breastfeeding Mothers - Andri, Juli; Maryanto, Qori; Padila, Padila; Sugiharno, Ramadhan Trybahari (JOSING: Journal of Nursing and Health, 2023)
This study aims to determine the effectiveness of oketani massage on smooth breastfeeding in breastfeeding mothers at the Basuki Rahmat Community Health Center, Bengkulu City. This research is quantitative research with a "Quasi-Experimental" research design. The study's results showed that the average value of breast milk production before being given the Oketani massage intervention was 5.07, and after being given the Oketani massage intervention, the average value was 6.33. The dependent t-test results obtained a deal (P) = 0.000 < (0.05). In conclusion, there is a difference in the flow of breast milk before and after the oketani massage on the smooth flow of breast milk in breastfeeding mothers in the working area of the Basuki Rahmat Health Center. Keywords: Breastfeeding Mother, Marmet Massage, Oketani Massage